Aqueous humor heat-shock protein 70, periostin, and irisin levels in patients with pseudoexfoliation syndrome - Guler, Mete; Aydin, Suleyman; Urfalioglu, Selma; Yardim, Meltem (Consel Brasil Oftalmologia, 2020)
Purpose: To measure humor heat-shock protein 70, periostin, and irisin levels in patients with pseudoexfoliation syndrome and cataract (without glaucoma), and compare them with those of patients with cataract but without Pseudoexfoliation. Methods: We examined 31 eyes of 31 patients with pseudoexfoliation and cataract (without glaucoma) and 30 eyes of 30 patients with cataract. We collected aqueous humor samples from all patients at the time of cataract surgery through a limbal paracentesis via a 25-gauge cannula mounted on a tuberculin syringe that received 100 to 150 mu L of aqueous humor. We measured levels of aqueous humor Heat shock protein 70, periostin, and irisin using enzyme-linked immunosorbent assay methods. Results: The age (p=0.221) and gender (p=0.530) means were similar between the pseudoexfoliation and control groups. The mean Heat shock protein 70 level (29.22 +/- 9.46 ng/mL; 17.88-74.46) in the pseudoexfoliation group was significantly higher than that in the control group (19.03 +/- 7.05 ng/mL; 9.93-35.52; p<0.0001). The mean periostin level was significantly higher (6017.32 +/- 1271.79 pg/mL; 3787.50-10803.57) in the pseudoexfoliation group than that in the control group (4073.63 +/- 1422.79 pg/mL; 2110.44-7490.64; p<0.0001). The mean irisin level (53.77 +/- 10.19 ng/mL; 29.46-71.16) was significantly higher than that in the control group (39.29 +/- 13.58 ng/mL; 19.41-70.56; p<0.0001). Conclusions: Heat shock protein 70, periostin, and irisin levels increase in the aqueous humor of patients with pseudoexfoliation without glaucoma.
Keywords: Aqueous humor; Irisin; HSP70; heat-shock proteins; Periostin; Pseudoexfoliation syndrome